Thermodynamic Interactions Due to Transfer of Amino Acids, Glycine and DL-Alanine from Water to Aqueous Mixture of Cationophilic Dipolar Aprotic N,N-Dimethyl Formamide - Roy, S.; Mahali, K.; Dolui, B.K. (Asian Journal of Chemistry, 2013)
In this paper, the standard free energies (DGt0(i)) and entropies (DSt0(i)) of transfer of homologous a-amino acids viz. glycine (gly), DL-alanine (ala), from water to aqueous mixture of cationophilic dipolar aprotic N,N-dimethyl formamide (DMF) have been calculated from solubility measurements at five equidistant temperatures i.e., from 15-35 ºC. The observed DGt0(i) and TDSt0(i) versus composition profiles are complicated because of the various interactional effects. The chemical transfer Gibbs energies (DG0t,ch(i)) and entropies (TDS0t,ch(i)) have been determined after elimination of cavity effect, estimated by the scaled particle theory and dipole-dipole interaction effects, estimated by the use of Keesom-orientation expression. The chemical contributions of transfer energetics of glycine and DL-alanine are guided by the composite effects of increased dispersion interaction, basicity and decreased acidity, hydrogen bonding, hydrophobic and hydrophilic interaction effects of aqueous DMF as compared to that of reference solvent, water.